1970
DOI: 10.1017/s0022112070002379
|View full text |Cite
|
Sign up to set email alerts
|

The stability of pipe flow Part 1. Asymptotic analysis for small wave-numbers

Abstract: The instability of Poiseuille flow in a pipe is considered for small disturbances. An asymptotic analysis is used which is similar to that found successful in plane Poiseuille flow. The disturbance is taken to travel in a spiral fashion, and comparison of the radial velocity component with the transverse component in the plane case shows a high degree of similarity, particularly near the critical point where the disturbance and primary flow travel with the same speed. Instability is found for azimuthal wave-nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

1971
1971
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…In the same way, Salwen and Grosch [10], Garg and Rouleau [11] and Gill [12] were not able to predict instability. Finally we have to mention the contradictory work of Graebel [13] who found instability at an azimuthal wavenumber n > 2. However, the numerical value reported by Graebel, cannot compare favorously with the usual experimental value (the critical value of the Reynolds number given by Graebel is of the order of 27).…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations
“…In the same way, Salwen and Grosch [10], Garg and Rouleau [11] and Gill [12] were not able to predict instability. Finally we have to mention the contradictory work of Graebel [13] who found instability at an azimuthal wavenumber n > 2. However, the numerical value reported by Graebel, cannot compare favorously with the usual experimental value (the critical value of the Reynolds number given by Graebel is of the order of 27).…”
Section: Introductionmentioning
confidence: 85%
“…The local potential for the differential equation (13) has been given in details by Mat and Platten [8], and will not be reconstructed here. However we shall outline the construction of the local potential for the non-axisymmetric case.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many theoretical investigations on the stability of Poiseuille flow with axisymmetric disturbances are carried out over many decades. Along with some asymptotic study for nonaxisymmetric disturbances, further numerical approaches show no linear instability for Poiseuille flow. An elaborate review of these works can be found in the works of Joseph, Drazin and Reid, and Schmid and Henningson …”
Section: Introductionmentioning
confidence: 89%
“…In addition, it has been found that the flow is least stable to the non-axisymmetric disturbance with azimuthal wavenumber n = 1 and is less stable to this disturbance than to an axisymmetric disturbance (n = 0), for both the wall and centre modes. The work of Graebel (1970), on the other hand, has shown that Poiseuille pipe flow is unstable to non-axisymmetric small disturbances at large axial wavenumbers, giving critical Reynolds numbers of the order of 10-100 for azimuthal wavenumbers of 2 and larger. As was pointed out by Salwen & Grosch (1972), this conflicting finding of Graebel is probably due to the breakdown of the approximation in his asymptotic solution, which is valid only for small axial wavenumbers andlarge Reynoldsnumbers.…”
Section: Introductionmentioning
confidence: 99%